THE CRIMINOLOGY OF CYBERCRIME; A STUDY OF ONLINE FINANCIAL FRAUD AND THE CHALLENGES FOR INDONESIAN LAW ENFORCEMENT - Hubbul Wathan; Lakshan Pradeep; Udara Jayasinghe; Thilina Samarasinghe (Cognitionis Civitatis et Politicae, 2025)
Indonesia faces escalating online financial fraud, particularly complex “Social Engineering/Mule Accounts” schemes, which strain law enforcement. A critical gap exists between the speed of these transnational digital crimes and the outdated operational capabilities of the Indonesian National Police (Polri). This study aimed to analyze the typology and high case attrition rates (unsolved cases) of online financial fraud and to critically evaluate the institutional and operational challenges faced by Indonesian law enforcement agencies in effectively investigating these offenses. sequential explanatory mixed-methods design was utilized, combining quantitative analysis of 2,150 reported fraud cases (2019–2024) with qualitative interviews (N=20) with police investigators, prosecutors, and banking compliance officers. Overall attrition stood at 68.4%, rising to 78.5% for mule account cases. The central finding is the Structural Lag Hypothesis: high attrition is a direct result of bureaucratic time lag, specifically “Jurisdictional Fragmentation” and “Slow Evidence Acquisition,” which grants criminals a critical 48-72 hour window to liquidate assets. The crime’s success is rooted in the police system’s procedural inertia, confirming that enforcement mechanisms are misaligned with the digital environment. The findings mandate urgent organizational reform, including the delegation of real-time data-sharing authority to local investigators to collapse this structural lag.